Black November Nollywood Movie: A Conflict Management Tool in The Niger Delta Region, Nigeria - Moses Igwe Bassey (PERSPEKTIF, 2023)
The Niger Delta has for decades been engulfed by oil-related conflicts which have had adverse effects on communities within the region, MNOCs, and the government. Although there are no clear statistics on the number of deaths arising from these conflicts, it is commonly acknowledged that these conflicts have resulted in a large number of deaths and the destruction of properties in the region (Emuedo et all., 2007). In response to this crisis, the government granted unconditional amnesty to the militants, set up developmental agencies, and introduced some policies but they have not achieved the desired outcome. The paper interrogated the use of the Nollywood movie Black November as a viable mechanism for conflict intervention and management tool in the ND. The issues bordering on the quest for emancipation from injustice, environmental degradation, deprivation, inhuman treatment, and negligence, are at the nexus of the agitations and militancy in the region. The objective was to highlight the problems in the region and give credence to the thematic concerns raised by the movie. The paper adopted the Media System Dependency (MSD) theory, which states the relationship between the media, the audience, and society. The method adopted is content analysis. Findings revealed that the movie had a great effect as it attracted international attention to the issues in the Niger Delta region. It concluded that the government and policymakers should take the lessons from this movie and respond to conflict early before they escalate into a crisis with lots of negative effects. It recommended that communities in the ND should be compensated for environmental degradation.